MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR MATEMATIKA MELALUI MODEL PEMBELAJARAN COOPERATIVE LEARNING TIPE PROBLEM BASED LEARNING - Meydiawati, Eva Ayu; Zainudin, M (Jurnal Teladan: Jurnal Ilmu Pendidikan dan Pembelajaran, 2020)
Abstract Mathematics Learning have to build an active communication process between teachers and students. But in fact student outcomes have not shown satisfactory results. Therefore, it is necessary to find a better learning models that can improve student achievement. The purpose of this resaerch is to improve the activity and learning of Mathematics through the implement of cooperative learning model type Problem based learning. The research method used is classroom action research using sprial reflection system of Kemmis and MC Taggart model that is done from action I, action II, and action III. This research was conducted from March 8, 2019 - March 29, 2019. The subjects of this research is the students of natural science class VIII-C SMP N 1 Babat academic year 2018/2019 as many as 35 student. The results of this research shows that the use of cooperative learning model of problem based learning type on the learning process of mathematics activity and the students score have increased from action I, action II, and action III. From the results of the study it can be concluded that the application of the cooperative learning model of the type of problem based learning has increased the activities and learning outcomes of Mathematics. Based on these conclusions, researchers recommend to implement the cooperative learning model of the type of problem based learning in other classes, so that improvement of learning can happen comprehensive.